Authentication gets personal with biometrics. - Ortega-Garcia, J. (IEEE Signal processing magazine)
Securing the exchange of intellectual property and providing protection to multimedia contents in distribution systems have enabled the advent of digital rights management (DRM) systems. User authentication, a key component of any DRM system, ensures that only those with specific rights are able to access the digital information. It is here that biometrics play an essential role. It reinforces security at all stages where customer authentication is needed. Biometric recognition, as a means of personal authentication, is an emerging signal processing area focused on increasing security and convenience of use in applications where users need to be securely identified. In this article, we outline the state-of-the-art of several popular biometric modalities and technologies and provide specific applications where biometric recognition may be beneficially incorporated. In addition, the article also discussed integration strategies of biometric authentication technologies into DRM systems that satisfy the needs and requirements of consumers, content providers, and payment brokers, securing delivery channels and contents.